VALUES OF RELIGIOUS MODERATION IN THE BOOK OF ISLAM THE CENTRAL WAY BY YUSUF QARDHAWI - Abdul Fikri; Mohamad Joko Susilo (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The social conditions of society in recent years have experienced various phenomena of intolerance that have given rise to different extreme, exclusive, and radical understandings. Some of these incidents are caused by narrowing and deviations in the knowledge of Islam. This study aims to determine the values of religious moderation in the book Islam The Central Way by Yusuf Qardhawi. Qualitative research uses a library research approach with the book Islam Jalan Tengah as a primary reference. Data collection using documentation study techniques. Data analysis techniques are carried out descriptively through data reduction, data display, and concluding stages. The results of this study concluded that the Values of Religious Moderation contained in the book Islam Jalan Tengah by Yusuf Qardhawi include: comprehensive values, relevance values, wisdom, universal values, adequacy values, and historical exploratory values.